2021
DOI: 10.3390/cancers13051109
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial, Archaea, and Viral Transcripts (BAVT) Expression in Gynecological Cancers and Correlation with Regulatory Regions of the Genome

Abstract: Bacteria, archaea, and viruses are associated with numerous human cancers. To date, microbiome variations in transcription have not been evaluated relative to upper female genital tract cancer risk. Our aim was to assess differences in bacterial, archaea, and viral transcript (BAVT) expression between different gynecological cancers and normal fallopian tubes. In this case-control study we performed RNA sequencing on 12 normal tubes, 112 serous ovarian cancers (HGSC) and 62 endometrioid endometrial cancers (EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Gonzalez-Bosquet et al in 2021, compared the microbiome of the female upper genital tract, in the environment of endometrial and ovarian cancer, with control samples (fallopian tubes) [ 63 ]. They measured the differences in bacterial, archaea, and viral transcripts (BAVT) between high-grade serum carcinoma (HGSC) and endometrial carcinoma (EEC), and found 93 BAVTs different in expression between the two types of gynecological tumors, of which 7 significant differences were noted: Salinibacter ruber , Bacillus tropicus , Pusillimonas sp.…”
Section: Composition Of the Endometrial And Uterine Microbiota In Pat...mentioning
confidence: 99%
See 2 more Smart Citations
“…Gonzalez-Bosquet et al in 2021, compared the microbiome of the female upper genital tract, in the environment of endometrial and ovarian cancer, with control samples (fallopian tubes) [ 63 ]. They measured the differences in bacterial, archaea, and viral transcripts (BAVT) between high-grade serum carcinoma (HGSC) and endometrial carcinoma (EEC), and found 93 BAVTs different in expression between the two types of gynecological tumors, of which 7 significant differences were noted: Salinibacter ruber , Bacillus tropicus , Pusillimonas sp.…”
Section: Composition Of the Endometrial And Uterine Microbiota In Pat...mentioning
confidence: 99%
“…They measured the differences in bacterial, archaea, and viral transcripts (BAVT) between high-grade serum carcinoma (HGSC) and endometrial carcinoma (EEC), and found 93 BAVTs different in expression between the two types of gynecological tumors, of which 7 significant differences were noted: Salinibacter ruber , Bacillus tropicus , Pusillimonas sp. ye3, Riemerella anatipestifer , Nostocales cyanobacterium HT-58-2, Orgyia pseudotsugata, and Corynebacterium pseudotuberculosis [ 63 ]. Nevertheless, in the controls, these BAVT species were the most abundant, while in the EEC samples—and even more so in the HGSC samples—BAVT expression was lower.…”
Section: Composition Of the Endometrial And Uterine Microbiota In Pat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Gonzalez-Bosquet et al also investigated the origins of these BAVTs, and they saw some human loci that harbour genetic material from these microorganisms; more exactly BAVTs were located within or close to genes or lncRNAS [ 38 ].…”
Section: Microbiome and Endometrial Cancermentioning
confidence: 99%
“…The Human Microbiome Project Consortium [ 9 , 10 ], has studied the human microbiome, including the normal microbiome of the vaginal environment. Additionally, there are a few studies about the microbiome in the upper genital tract and its association with gynecological (uterine and ovarian) cancers [ 11 , 12 ]. However, very little is known about potential mechanisms associated with malignant transformation in microbiome-associated gynecological cancer, except for HPV-induced cervical cancer [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%